Genetic Polymorphism of GHR, LEP and MSTN Genes in Surti Goats from Organized Farm - Pandya, Gaurav M.; Ramani, Umed V.; Tyagi, Kuldeep K.; Dangar, Nikhil S.; Janmeda, Mamta (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Genetic studies pertaining to genes related to growth parameters can give idea about growth, meat as well as milk production performance of the animals in advance. Surti is considered as a dual purpose goat breed mainly of South Gujarat region. The aim of the present study was to know the genetic polymorphism in growth related genes, viz., growth hormone receptor (GHR), leptin (LEP) and myostatin (MSTN) through PCR-RFLP technique. The blood samples were collected from 62 Surti goats and DNA was extracted. Amplification of the genes was carried out using suitable primers. The PCR products of GHR, LEP and MSTN were digested with AvaII, HinfI and HaeIII enzymes, respectively. PCR products were found to be monomorphic on digestion.